Wilson's disease: A Comprehensive Review of Genetics, Pathophysiology, Clinical Symptoms, Diagnostic Techniques and Current Treatment - Natalia Wdowiak; Martyna Choinka; Agata Konopka; Zuzanna Szczepaniak; Kinga Adamska (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Wilson's disease (WD) is a genetic disease, inherited in an autosomal recessive manner, caused by a mutation in the ATP7B gene, which results in impaired excretion of copper in the bile. This causes the accumulation of copper in various tissues and organs, leading to their damage. The range and severity of symptoms are wide, so diagnosis is difficult and requires a high index of suspicion. The most common clinical symptoms are hepatic and neuropsychiatric symptoms. Diagnosis is based primarily on clinical suspicion, typical symptoms and reduced serum ceruloplasmin concentration. Treatment includes pharmacological therapies, and in some cases liver transplantation is necessary. Wilson's disease, if left untreated, inevitably leads to serious disability and death.   Purpose of the work: This study aims to review and characterize the clinical and pathophysiological aspects of Wilson's disease.   Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: Wilson's disease, Copper metabolism, Copper toxicity, ATP7B, Ceruloplasmin, Gene Mutation   Results: Wilson's disease is a rare genetic disorder that can lead to severe disability and even death. For this reason, rapid diagnosis and appropriately selected and individualized treatment play a key role. Wilson's disease remains a major diagnostic challenge, but new techniques for its diagnosis, such as genotype analysis, mainly through sequencing, as well as newborn screening, may significantly improve patient prognosis in the future.